Enhancement of PEO Performance in Reducing Turbulent Flow Drag with the Addition of SDBS Anionic Surfactant - Fakhrulddin, Sarmad K.; Abdulbari, Hayder A. (Kuwait University, 2017)
Polyethylene Oxide (PEO) is a non-ionic polymer which has been used widely as a drag reduction (DR) agent. Nevertheless, its ability to reduce drag in turbulent flow is yet limited. Thus, in this paper, a study to improve the ability of PEO to reduce drag in a turbulent flow through the addition of an anionic surfactant (Sodium dodecyl benzene sulfonate-SDBS) is presented. The various concentration range of PEO (10, 20, 40 and 60 ppm) and SDBS (100, 200, 400, and 500 ppm) was studied. The physical properties, viscosity, and electrical conductivity were measured to evaluate interaction in a complex solution. The electrical conductivity measurements confirmed that the interaction between the polymer-surfactant solutions takes place between the CAC-PSP points. The drag reduction measurements were done using a Rotating Disk Apparatus (RDA). The RDA results showed substantial findings when the anionic surfactant-polymer solution was compared to the pure polymer solution. The interaction between the polymer and the surfactant results in transforming the polymer from coil to straight-like body which enhanced the polymer drag reduction ability. The PEO-SDBS solution showed the highest DR of 50 %, at a mixture concentration of 60 ppm of PEO with 200 ppm of SDBS. Nonetheless, at higher concentrations, the DR value dropped due to the increase in the relative viscosity of the solution which enhanced the resistance to the flow.